Trichoderma spp.: potencial para biocontrole de patógenos habitantes do solo e indução de resistência em feijoeiro - Sarzi, Janaina Silva (2023)
Among the factors that interfere with the development and yield of bean crops are diseases caused by soil-inhabiting pathogens, such as gray stem rot, caused by Macrophomina phaseolina and Fusarium wilt, caused by Fusarium oxysporum. Biological control of phytopathogens has been one of the most effective strategies in the management of various diseases. Therefore, the general objective of the work was to evaluate the activity of Trichoderma spp. in the biocontrol of soil- inhabiting pathogens and induction of resistance in bean. The specific objectives correspond to each study carried out, which consisted of: a) evaluating the sanitary and physiological quality of bean seeds treated with conidia suspension and culture filtrates of Trichoderma spp. and the effect of the antagonist on the health quality of bean seeds inoculated with Fusarium oxysporum and Macrophomina phaseolina; b) evaluate the effect of Trichoderma spp., in the form of conidial suspension or culture filtrate, on the biocontrol of M. phaseolina and induction of resistance in bean; c) evaluate the effect of Trichoderma spp., in the form of culture filtrate or conidial suspension, on the biocontrol of F. oxysporum and the induction of resistance in bean; d) evaluate the effect of Trichoderma spp., in the form of conidial suspension and culture filtrate, on the biocontrol of M. phaseolina and F. oxysporum and their effects on yield components in bean; e) evaluate the effect of transgenerational priming of characteristics related to the growth and defense system of bean seedlings against attack by Macrophomina phaseolina and Fusarium oxysporum induced by Trichoderma virens culture filtrate. The sanitary and physiological quality of the seeds was evaluated through health tests, health tests with inoculation of F. oxysporum and M. phaseolina and germination test using the paper roll incubation method. The antifungal activity of the antagonist on the pathogens was evaluated using direct confrontation, volatile metabolites and culture filtrate tests, and at the end of the tests the percentage of inhibition of mycelial growth of the pathogens was determined. For in vivo experiments, three isolates of Trichoderma spp. were selected and used in the form of conidial suspension and culture filtrate to treat bean seeds. In vivo studies of the pathogens were performed in separate experiments. The suspension of conidia of Trichoderma spp. obtained a higher percentage of reduction in the incidence of the pathogen in relation to culture filtrates, in seed health tests. Culture filtrates of Eco, TR4 and SC isolates were the most promising in relation to seedling growth and dry mass analyses. Treatments with Trichoderma spp. showed an effect on the in vitro biocontrol of M. phaseolina and F. oxysporum. The activity of the antioxidant enzymes, superoxide dismutase and guaiacol peroxidase, was enhanced and hydrogen peroxide levels were controlled with treatments of Trichoderma spp. Treatments with Trichoderma spp. ensured a lower severity of gray stem rot and Fusarium wilt. Treatments with Trichoderma spp. contributed to the increase in morphological characteristics in studies of both pathogens, as well as showing increases in the number of grains per plant and grain mass per plant. The use of T. virens culture filtrate generated a transgenerational priming effect in inducing resistance in bean seedlings to M. phaseolina.